CHARACTER EDUCATION AS A MORAL FOUNDATION FOR CHILDREN IN THE DIGITAL ERA (Literature Conceptual Review) - Wartinah, Wartinah; Hidayat, Nur (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The development of the digital era and globalization has a significant impact on children's lives, including in moral, social, and spiritual aspects. The rise of unfiltered digital content, identity crises, and permissive culture are serious challenges in the formation of noble morals of the younger generation. In this context, character education is an urgent need that must be systematically integrated into the education system and children's daily lives. The formulation of the problem in this study is how the urgency and relevance of character education in shaping children's morals in the midst of the rapid flow of globalization and digitalization. This research aims to analyze the concept, urgency, and implementation of character education in the contemporary context. The approach used is qualitative with the library research method, which examines classical and contemporary literature on character values and implementation strategies. The results of the study show that character education has a central role in instilling values such as honesty, responsibility, empathy, discipline, tolerance, and religiosity. These values serve as a moral foundation that strengthens children's resilience in the face of various negative influences. Character education must be carried out consistently and continuously in the family, school, and community environment. The implications of this study confirm that character education is a crucial long-term investment in shaping a generation that is not only intellectually intelligent, but also morally strong and ready to face global challenges without losing identity.